Strategi Investasi di Bursa Saham - Suryanto, Suryanto (Journal the Winners: Economics, Business, Management, and Information System Journal, 2002)
Investor uses strategy and a certain technique to analyze different situation and condition happened between one and other exchange companies. The strategy is developed based on experiences, research result, analysis, and market surveys in a certain period. Articel is the first part ofÂ  three series which presents, evaluate, examine of the strategy, and consider tactics in sharing share on the market. It is concluded that the investor should use money as loan that should be payed as soon as possible for the sake of its interests.Â